(untitled) (World of finance, 2022)
Introduction. The growing inequality in society and the inability of the market economy to reduce its manifestations, in terms of uneven distribution of income and wealth, encourage the state to address this problem as a guarantor of welfare. Hence there is a need for scientific substantiation of the theoretical foundations of the application of various economic instruments for regulating income and wealth in the society, especially – fiscal. The purpose of the article is the theoretical substantiation of the fiscal mechanism of regulation of incomes and wealth in society and the definition and description of the role of taxes and expenditures of the state in the functioning of such a mechanism. Results. The study substantiates that the fiscal mechanism for regulating income and wealth in society is based on the movement of financial resources between the subjects of such distribution, which include citizens, corporations and the state. The tax evasion and transition to the shadow economy are the limiting factors in the use of taxes as a tool to reduce inequality in society. Conclusions. The personal income tax has the greatest regulatory potential for the formation of personal income. The corporate taxation is an integral part of reducing the asymmetries of income and wealth distribution in society. The role and mechanism of using public expenditures to regulate income inequality depends on the state of socio-economic development of the state and the wealth of the population. It is determined by the type of expenditures that are stimulated or limited by the state.